Improving oral communication skills in early childhood education through the Numbered Heads Together (NHT) cooperative strategy - Desi Laila (Science Center Group, 2025)
Background: Oral communication skills represent a fundamental component of early childhood development, as they support cognitive growth, social interaction, and future academic readiness. However, many early childhood classrooms still demonstrate unequal participation patterns, where only a small proportion of learners actively engage in speaking activities. Cooperative learning strategies, particularly the Numbered Heads Together (NHT) model, offer structured participation mechanisms that may promote equitable speaking opportunities and enhance children’s communication competence. Objective: This study aimed to improve oral communication skills among early childhood learners through the implementation of the Numbered Heads Together cooperative strategy in classroom learning. Methods: The study employed a classroom action research design conducted in two cycles involving 24 early childhood learners aged 6–7 years. Each cycle consisted of planning, action, observation, and reflection phases. The intervention integrated structured group discussion and random number calling to ensure equal speaking opportunities. Data were collected through structured observation sheets, speaking performance rubrics, field notes, and video documentation. Quantitative data were analyzed using normalized gain scores, while qualitative data were examined through thematic reflection analysis. Results: The findings indicated progressive improvement in children’s oral communication performance across cycles. The normalized gain score increased from 0.42 (moderate improvement) in Cycle I to 0.71 (high improvement) in Cycle II. The proportion of actively participating students increased significantly, while passive behavior decreased markedly. Improvements were observed in fluency, vocabulary use, pronunciation clarity, responsiveness, and speaking confidence. The cooperative accountability mechanism ensured equitable participation and reduced speaking anxiety among learners. Conclusion: The Numbered Heads Together cooperative strategy effectively enhanced oral communication skills in early childhood education through structured collaboration and equal speaking distribution. The findings suggest that systematic cooperative participation models can serve as practical pedagogical solutions for strengthening early childhood oral communication competence.